Exact solitonic solutions for optical media with χ(2) nonlinearity and PT-symmetric potentials - Abdullaev, Fatkhulla Kh.; Umarov, Bakhram (Institute of Physics Publishing (UK), 2014)
We study the χ(2) system of equations with the PT-symmetric potentials. We obtain exact solitary wave solutions for this system for some forms of the PT-symmetric potentials.